The Nonhuman in American Literary Naturalism - Danielsson, Karin M.; Brandt, Kenneth K. (Lexington Books, 2023)
The Nonhuman in American Literary Naturalism responds to a need to expand and refine the connections among nonhuman studies and American literary naturalism and to productively expand the scholarly discourse surrounding this vital movement in American literary history. This collection focuses on that which becomes visible when the human subject is skirted, or moved off-center: in other words, the representation of nonhuman animals and other vital or inert species, things, entities, cityscapes and seascapes, that play an important part in American literary naturalism. Informed by animal studies, ecocriticism, posthumanism, new materialism, and other recent theoretical perspectives, the essays in this collection discuss early naturalist texts as well as more recent naturalistic-oriented authors.